Influência dos defeitos nas funcionalidades elétricas de ZnO, AgO e polianilina - Paiva, Aline Bastos de (Universidade Federal de São Carlos, 2023)
The optical and electrical properties in a semiconductor can be modeled by structural defects. In this thesis, we study the influence of defects on the optical and electronic properties of organic and inorganic semiconductors in thin films form. Polyaniline (PANI), an organic conductive polymer, was synthesized by the chemical route and deposited on a glass substrate by casting technique. Though, the zinc and silver oxide films were produced by the spray pyrolysis technique. The zinc and silver concentrations were controlled using zinc acetate e silver nitrate concentrations in process synthesis. The films are polycrystalline, and it is noted that phase segregation when the silver nitrate is higher them 5%. The film has grown up just with silver nitrate was exhibit two phases: metallic silver (Ag) in the cubic structure and silver oxide (AgO) in the monoclinic structure. In ternary films, the absorption in the visible region referring to the surface plasmons of Ag is observed. In terms of luminescent properties, two emission bands are present: one, in the ultraviolet region, referring to emissions close to the conduction and valence bands, and another in the visible region, referring to defects. The PANI film has absorptions at 440 nm and 800 nm, characteristic of the salt emeraldine oxidation state, and emits in a broad visible band. The dynamics of photoconduction in PANI were analyzed using a rate equation model. While PANI and silver films showed photoresponses in the order of seconds, films containing Zn showed slow and persistent responses. We also observed the resistive memory effect on the longitudinal transport of ZnO when stimulated by a periodically applied voltage. The memory effect is dependent on the scan period and temperature, and we identified a critical period in the memory effect of 120 min. An increase in the memory effect is also observed with increasing temperature, modeled in terms of the energy barriers present in the crystallite boundaries of the film.
Influence of defects on the electrical functionalities of ZnO, AgO and polyaniline
Keywords: Polianilina; Defeitos; Fotocondução; Memresistor; Polyaniline; ZnO; AgO; Defects; Photoconduction; Memresistor; CIENCIAS EXATAS E DA TERRA::FISICA